Long-Term Survival after Primary Ewing's Sarcoma of the Skull with Intracranial Extension - Rainov, Nikolai G.; Haritonov, Dimitar; Heidecke, Volkmar (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2023)
Background and Objective Primary Ewing's sarcoma of the skull is a very rare malignant neoplasm, predominantly occurring in children and adolescents. We describe here the clinical, neuroradiologic, and histopathologic features of a patient with primary Ewing's sarcoma of the skull and discuss the standards of therapy for this type of tumor.Clinical Presentation This 18-year-old male patient presented with a primary Ewing's sarcoma of the skull, involving the dura of the frontal and parietal lobes of the left cerebral hemisphere. He was treated with gross total surgical excision of tumor, skull reconstruction, chemotherapy, and irradiation. Twelve years after the surgery, the patient has no evidence of local recurrence or distant metastases. Radical surgical excision of the primary tumor with safety margins is thought to play a role in the favorable clinical course.Conclusion The presented case is the longest surviving patient after treatment of primary Ewing's sarcoma of the skull bone. This rare type of tumor may allow better survival rates under adequate management than sarcoma elsewhere in the body.
Keywords: Ewing's sarcoma; cranial sarcoma; malignant bone tumor